2018
DOI: 10.3389/fphar.2018.00094
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Direct Current Stimulation Block Remifentanil-Induced Hyperalgesia: A Randomized, Double-Blind Clinical Trial

Abstract: Background: Remifentanil-induced hyperalgesia (r-IH) involves an imbalance in the inhibitory and excitatory systems. As the transcranial Direct Current Stimulation (tDCS) modulates the thalamocortical synapses in a top-down manner, we hypothesized that the active (a)-t-DCS would be more effective than sham(s)-tDCS to prevent r-IH. We used an experimental paradigm to induce temporal summation of pain utilizing a repetitive cold test (rCOLDT) assessed by the Numerical Pain Score (NPS 0-10) and we evaluated the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 62 publications
(68 reference statements)
2
29
1
Order By: Relevance
“…Few studies investigated the application of tDCS to counter-regulate the dysfunction in the DPIS induced by opioids. In healthy subjects in an experimental model, we showed that the tDCS applied over M1 blocked the dysfunction caused by remifentanil on the inhibitory pathways or up-regulation of the pain-facilitating pathways (Braulio et al, 2018). This effect of tDCS was demonstrated to prevent both the disengagement of the DPIS and the summation effect on pain scores during the cold pressor test (Braulio et al, 2018).…”
Section: Evidence Of Tdcs Impact On Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies investigated the application of tDCS to counter-regulate the dysfunction in the DPIS induced by opioids. In healthy subjects in an experimental model, we showed that the tDCS applied over M1 blocked the dysfunction caused by remifentanil on the inhibitory pathways or up-regulation of the pain-facilitating pathways (Braulio et al, 2018). This effect of tDCS was demonstrated to prevent both the disengagement of the DPIS and the summation effect on pain scores during the cold pressor test (Braulio et al, 2018).…”
Section: Evidence Of Tdcs Impact On Painmentioning
confidence: 99%
“…In healthy subjects in an experimental model, we showed that the tDCS applied over M1 blocked the dysfunction caused by remifentanil on the inhibitory pathways or up-regulation of the pain-facilitating pathways (Braulio et al, 2018). This effect of tDCS was demonstrated to prevent both the disengagement of the DPIS and the summation effect on pain scores during the cold pressor test (Braulio et al, 2018). When focusing on opioid dependence, a recent review (Gallucci et al, 2019) found only one study that used tDCS.…”
Section: Evidence Of Tdcs Impact On Painmentioning
confidence: 99%
“…This positive scenario will allow us to determine specific biomarkers (e.g., TSPS, CPM, TMS TSPS results may indicate that both interventions and EEG) that could help to predict treatment response in future clinical trials. Preliminary data suggested a positive effect of tDCS and exercise alone in TSPS [15, 86, 87] and CPM [88], however, so far, these specific markers have not been used to guide specific interventions. Furthermore, with these results regarding TMS and EEG, it is possible to indirectly assess how changes in the endogenous pain regulatory control are related to alterations in abnormal cortical excitability [81] as indexed by TMS and thalamic dysrhythmia [83, 89, 90] as indexed by EEG.…”
Section: Understanding the Neural Effects Of Tdcs Combined With Aerobmentioning
confidence: 99%
“…Strategy I: effects of tDCS on CPM in patients with chronic pain - effect size (ES) of 0.79[98]. Strategy II: effects of tDCS on CPM in healthy volunteers - pooled ES of 1.02 [87, 91, 99, 100] and Strategy III: effect of exercise on CPM in chronic pain - ES of 0.78[86]. Based on this analysis, a conservative approach with the lowest ES was chosen using an ES of 0.78.…”
Section: Design Of a Combined Treatmentmentioning
confidence: 99%
“…Nonetheless, many studies have demonstrated that remifentanil could enhance postoperative analgesic consumption and cause pain hypersensitivity. However, its mechanism and effective therapy are still unclear 7,8. This study focused on the mechanism of remifentanil-induced postoperative hyperalgesia; we are hoping to provide new ideas for the treatment and prevention of remifentanil-induced postoperative hyperalgesia to relieve patients’ pain.…”
Section: Introductionmentioning
confidence: 99%